Natural triploidy in Astyanax scabripinnis (Pisces, Characidae) and simultaneous occurrence of macro B-chromosomes - Maistro, E. Luis [UNESP]; Lúcia Dias, A. [UNESP]; Foresti, F. [UNESP]; Oliveira, C. [UNESP]; Filho, O. Moreira [UNESP] (Firenze University Press, 1994)
The occurrence of natural triploidy in two specimens of Astyanax scabripinnis collected in the Araquá river and in the Córrego das Pedras stream, respectively, is noticed. The triploid specimen from the Araquá river presented one macro B-chromosome and the triploid specimen from Córrego das Pedras stream presented two macro B-chromosomes. The C-banding performed in the specimen from the Araquá river confirmed the triploidy and showed that the macro B-chromosome was entirely heterochromatic. Ag-NOR characterization showed two chromosomes involved in the nucleolar activity in both specimens. Some aspects related to the origin of triploid fishes are described. © 1994 Taylor & Francis Group, LLC.
Keywords: Astyanax scabripinnis; B-chromosomes; C-banding; Fish cytogenetics; Natural triploidy